Sexual dysfunction in patients with polycystic ovary syndrome in Malaysia - Dashti, Sareh; Abd Latiff, Latiffah; Abdul Hamid, Habibah; Mohamad Sani, Suriani; Akhtari-Zavare, Mehrnoosh; Abu Bakar, Azrin Shah; Sabri, Nur Amirah Inani; Ismail, Maimunah; Esfehani, Ali Jafarzadeh (Asian Pacific Organization for Cancer Prevention, 2016)
Background: Polycystic ovary syndrome (PCOS) is a combination of chronic anovulation, obesity, and hyperandrogenism and can affect sexual function in women of reproductive age. It is also associated with endometrial cancer. Our aim was to evaluate the frequency and predisposing factors of sexual dysfunction in PCOS patients. Materials and methods: In this cross-sectional study, 16 married women with a definite diagnosis of PCOS were recruited. Sexual function was assessed in the domains of desire, arousal, lubrication, orgasm, satisfaction and pain using the female sexual function index (FSFI) questionnaire. Patients were also assessed for mental health using the depression, anxiety and stress (DASS-21) questionnaire. Presence of hirsutism was assessed using the Ferriman-Gallwey (FG) scoring system. Demographic data were obtained from patients during in-person interview. Results: Sexual dysfunction was present in 62.5% of patients with the domains of arousal and lubrication particularly affected (93.8% and 87.5%, respectively). Patients with symptoms of depression and anxiety were significantly more likely to suffer sexual dysfunction than those without these symptoms (p=0.04 and p=0.03 respectively). Patients with stress symptoms reported higher orgasm dysfunction than those without (p=0.02). No significant difference in any of the FSFI score domains was observed between patients with and without hirsutism. Conclusions: PCOS patients markedly suffer from sexual dysfunction and therefore it seems appropriate to be screened for intervention. Poor mental health conditions that may be the result of infertility or other complications of PCOS should also be considered as curable causes of sexual dysfunction in these patients.